2017
DOI: 10.4293/jsls.2016.00095
|View full text |Cite
|
Sign up to set email alerts
|

Power Morcellation Using a Contained Bag System

Abstract: Background and Objectives:The well-known advantages of minimally invasive surgery make the approach well suited for hysterectomy and other gynecological procedures. The removal of specimens excised during surgery has been a challenge that has been answered by the use of power morcellation. With this study we sought to assess the feasibility of power morcellation within a specimen bag.Methods:This was a retrospective cohort study including patients from a private practice in suburban Chicago, Illinois, who unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…However, an in vitro study demonstrated that the risk of leakage and tissue dissemination still exists, depending on the insufflation pressure and material type of the bag [53], and the case of Süleyman Salman confirmed this issue [54]. Another in vivo study showed that some types of bags seem to be safe [55], [56], but the existing bags were not designed for power morcellation and, thus, risk spillage in the case of multiport laparoscopy. The authors of that study suggested that the absence of leakage be assessed by visual inspection.…”
Section: Iatrogenic Adenomyoma [13] [14] [15]mentioning
confidence: 99%
“…However, an in vitro study demonstrated that the risk of leakage and tissue dissemination still exists, depending on the insufflation pressure and material type of the bag [53], and the case of Süleyman Salman confirmed this issue [54]. Another in vivo study showed that some types of bags seem to be safe [55], [56], but the existing bags were not designed for power morcellation and, thus, risk spillage in the case of multiport laparoscopy. The authors of that study suggested that the absence of leakage be assessed by visual inspection.…”
Section: Iatrogenic Adenomyoma [13] [14] [15]mentioning
confidence: 99%
“…Therefore, in this study, we reported an NMC system with the aim of realizing the integration of the containment bag and laparoscopic trocars to form a completely sealed containment barrier that prevents the spillage of liquids and tissue from the time the uterine tissue is morcellated and encapsulated in the system. Several protected techniques by using endobag systems for UL power morcellation have been described in the literatures (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Although these technologies can play a protective role, there are still three major shortcomings.…”
Section: Discussionmentioning
confidence: 99%
“…However, the usage of containment bags is limited to a determined uterine weight[ 27 ]. At this regard, a study reported successful in-bag contained procedures of power morcellation for samples varying from 300 to 2134 g, with no bag rupture or bag-associated complications[ 14 ]. To date, few studies tested the use of in-bag contained extracorporeal manual morcellation for large uteri after TLH, with the largest specimen weighing 1930 g[ 20 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such procedure was firstly described by Shibley[ 9 ] that used power morcellation to remove a uterus inside a bowel isolation bag. Different authors described feasible variants of such procedure, without major complications[ 10 - 14 ]. Retrospective studies showed that contained power morcellation necessitates an extra operative time of 20-26 minutes in comparison to uncontained power morcellation, with similar postoperative results[ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%